IMPLEMENTASI MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN PKn UNTUK MENINGKATKAN PARTISIPASI WARGA NEGARA PADA SISWA SEKOLAH DASAR - Siti Chomsiyatul Ma'rifah; Shofiyati Fadillah; Sri Sri Ningsih; Zafira Rifatil Badri; Mujtahidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in civics learning and the civic participation of elementary school students during project-based learning. The study used a qualitative approach with descriptive methods. The study was conducted at SDN Socah 2, with fifth and sixth-grade students selected using purposive sampling. Data collection techniques included observation, interviews, documentation, and a student participation questionnaire. Data analysis was conducted using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the PjBL model was able to create more active, interactive, and contextual learning through project activities such as poster creation in fifth grade and brochures in sixth grade. Student participation was evident in their active participation in discussions, their ability to work together, their responsibility in completing assignments, and their courage to express their opinions. The questionnaire results showed an average student participation score of 74.7, with a participation percentage reaching 93.38%, which is categorized as very good. Despite constraints such as time constraints and differences in student collaboration skills, the PjBL model was able to provide meaningful learning experiences and encourage the application of civic values ​​in everyday life.